In Vitro Culture Technology for the Production of Secondary Metabolites and the Development of Plants That are Resistant to Climate Change - Sutini; Widiwurjani; Augustien, Nora; Guniarti; Pribadi, Didik Huswo; Purwanto, Djoko Agus; Muslihatin, Wirda (Future Science)
Climate change that we are experiencing today is triggered by global warming which causes air temperature to rise, drought-land degradation, fluctuating rainfall, floods, landslides, pollution, and rising sea levels. In the agricultural sector, this results in decreased soil fertility, decreased agricultural yields, physiological effects on plants, weed disturbances and attacks by pests. Therefore, the estimation strategy and the provision of adaptive technology include applying plant-invitro culture technology that can adapt to climate change. The problem of this paper is the decrease in productivity and the stagnation of secondary metabolite biomass production in plants. This problem can be overcome by adapting in vitro culture techniques to produce secondary metabolites and plant development. In vitro culture has advantages including it does not depend on climate, altitude, weather and environmental temperature. The aim of this study was to adapt the in vitro plant culture techniques to obtain secondary metabolites and adaptive plant development. The method used is a review of the literature related to in vitro culture techniques that can produce secondary metabolite biomass and the development of various plant varieties. The conclusion of this research is that in vitro culture techniques can produce a variety of secondary metabolites and adaptive plants. The implication of this paper is to obtain a variety of secondary metabolite biomass and various plants that are resistant to climate change.